Provincial Analysis of Years of Life Lost and Economic Impact of Heart Disease Among the Working-Age Population in Indonesia (2018-2023) - Verdiana, Antokalina Sari; Cerinda, Mitha; Mansur, Rizal; Cahyani, Fentya Yumna (Riviera Publishing, 2026)
Heart disease is the leading cause of premature death in Indonesia, significantly impacting both health and the economy. In 2023, BPJS Kesehatan allocated IDR 23.52 trillion for heart disease treatment, the highest expenditure among all diseases. This study aims to quantify the burden of heart disease by calculating years of life lost (YLL) and productivity costs, highlighting the need for effective prevention strategies. Using BPJS Kesehatan mortality data from 2018–2023, covering 218,279 individuals, this study identified heart disease-related deaths and calculated YLL using the Burden of Disease framework and World Health Organization (WHO) life expectancy tables. The analysis focused on the working-age population (15–64 years) at national and provincial levels, linking YLL data to provincial minimum wages, with a gender-based analysis. Significant variations in productivity losses due to heart disease were found across provinces. Central Java had the highest loss (IDR 9.39 trillion), followed by East Java (IDR 9.20 trillion). Jakarta, with the highest minimum wage, had a comparatively smaller loss (IDR 7.92 trillion). Males accounted for 65% of productivity losses. These findings underscore the need for targeted health interventions to reduce YLL and mitigate economic burdens through early detection, improved healthcare access, and public health campaigns.